GROWTH AND MORPHODIFFERENCIATION ON THE TISSUES PROTEIN PROFILE AND PHOSPHATASES ACTIVITY IN ACHATINA FULICA (FERUSSAC) (GASTROPODA : PULMONATA) - INDRA, D.; RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Achatina fillica (Ferusale a stylommatophoran molluscan pest of agriculture and horticultural crops, has been found to be distributed ubiquitously in different parts of India (Singh. 1986). The protein characterization on its developmental profile, revealed its heterogeneous distribution in the albumin gland. digestive gland, body mass muscle, foot muscle and hemolymph. The increased concentration of protein in these tissues during reproductive and postreproductive stages revealed its synthesis. The enhanced activity of phosphatases in the reproductive and postreproductive phases attribute their role in differentiation and development. The electropherograms of immature. reproductive and postreproductive stages revealed the Specific increase of high molecular weight fractions in all tissues, while an increase of both low and high molecular weight fractions in albumin gland. The heterogeneity of protein content in the tissues and the temporal changes in enzyme activity may infer the phasic expression of genetic induction and protein synthesis during growth and morphodifferentiation of the snails.